2022
DOI: 10.1002/smll.202205191
|View full text |Cite
|
Sign up to set email alerts
|

Simulation‐Assisted Localized DNA Logical Circuits for Cancer Biomarkers Detection and Imaging

Abstract: DNA‐based nanodevices equipped with localized modules have been promising probes for biomarker detection. Such devices heavily rely on the intramolecular hybridization reaction. However, there is a lack of mechanistic insights into this reaction that limits the sensing speed and sensitivity. A coarse‐grained model is utilized to simulate the intramolecular hybridization of localized DNA circuits (LDCs) not only optimizing the performance, but also providing mechanistic insights into the hybridization reaction.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(16 citation statements)
references
References 52 publications
0
13
0
Order By: Relevance
“…To the best of our knowledge, this sensitivity is comparable and even superior to most of previously reported fluorescent sensors or methods (Table S2, Supporting Information). [33][34][35][36][37][38][39][40] The selectivity of APE1 detection was also investigated by testing the signal response resulted from several protein and enzymes. As shown in Figure 5D, compared with APE1 that resulted in strong fluorescence signal, the other analytes such as flap endonuclease 1 (FEN1), T4 ligase, exonuclease III (Exo III), Exo I, glucose oxidase (GOx), alkaline phosphatase (ALP), bovine serum albumin (BSA), and trypsin only caused weak detectable signal which were close to the blank background.…”
Section: Sensitivity and Selectivity Of Ape1 Detectionmentioning
confidence: 99%
“…To the best of our knowledge, this sensitivity is comparable and even superior to most of previously reported fluorescent sensors or methods (Table S2, Supporting Information). [33][34][35][36][37][38][39][40] The selectivity of APE1 detection was also investigated by testing the signal response resulted from several protein and enzymes. As shown in Figure 5D, compared with APE1 that resulted in strong fluorescence signal, the other analytes such as flap endonuclease 1 (FEN1), T4 ligase, exonuclease III (Exo III), Exo I, glucose oxidase (GOx), alkaline phosphatase (ALP), bovine serum albumin (BSA), and trypsin only caused weak detectable signal which were close to the blank background.…”
Section: Sensitivity and Selectivity Of Ape1 Detectionmentioning
confidence: 99%
“…Furthermore, APE1 is frequently found to be overexpressed in various cancer cells, making it a potential cancer biomarker. 18,19 Considering the recognition of multiple cancer biomarkers that are overexpressed in tumor cells is crucial for precise cancer diagnosis, we believe it is significant to utilize APE1 in conjunction with other biomarkers, such as miRNA, to create a dual-trigger “AND” logic gate for in vitro detection and in vivo biological imaging. 16,20 This innovative approach of incorporating APE1 in constructing biosensors has the potential to simultaneously establish sensitive and logic-controllable dual-trigger detection systems for precise tumor diagnosis.…”
Section: Introductionmentioning
confidence: 99%
“…Research has shown that localized DNA functional modules increase the local concentration, promoting interactions between DNA strands. However, irrational localization strategies offer limited improvement in the hybridization efficiency between DNA strands compared to nonlocalized approaches. Coarse-grained models have been widely employed to simulate and analyze the DNA structural properties, providing insights into the mechanical characteristics of DNA behaviors. The simplicity of interactions between DNA strands and the predictability of mechanical properties makes it possible to use coarse-grained models to rationalize numerous synthetic structures …”
Section: Introductionmentioning
confidence: 99%